2010
DOI: 10.1158/1535-7163.mct-09-0693
|View full text |Cite
|
Sign up to set email alerts
|

A Fine-Needle Aspirate–Based Vulnerability Assay Identifies Polo-Like Kinase 1 as a Mediator of Gemcitabine Resistance in Pancreatic Cancer

Abstract: This work aimed to discover targets for combination treatment with gemcitabine in pancreatic cancer. We selected 11 tumors from our live collection of freshly generated pancreatic cancer xenografts with known degrees of varying gemcitabine sensitivity. We briefly (6 h) exposed fine-needle aspiration material to control vehicle or gemcitabine (1 μmol/L) and compared the gene expression of the treated and untreated samples using a reverse transcription-PCR-based, customized low-density array with 45 target genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 25 publications
1
53
0
1
Order By: Relevance
“…Eluted peptides were lyophilized and fractionated at 1 ml/min on a 9.4-by 200-mm 5-m-particle polysulfoethyl A strong cation exchange (SCX) column (PolyLC) using a 70-min gradient from 0 to 75 mM KCl, with 350 mM KCl for 38 min in 5 mM KH 2 PO 4 (pH 2.65), and 30% acetonitrile. Eighteen fractions with 6 ml eluate were collected, desalted on a Sep-Pak Vac 1-ml C 18 cartridge, and lyophilized as described above before. In the desalting step, the last eight fractions were reduced to four fractions by loading two fractions on one cartridge, giving a total of 14 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Eluted peptides were lyophilized and fractionated at 1 ml/min on a 9.4-by 200-mm 5-m-particle polysulfoethyl A strong cation exchange (SCX) column (PolyLC) using a 70-min gradient from 0 to 75 mM KCl, with 350 mM KCl for 38 min in 5 mM KH 2 PO 4 (pH 2.65), and 30% acetonitrile. Eighteen fractions with 6 ml eluate were collected, desalted on a Sep-Pak Vac 1-ml C 18 cartridge, and lyophilized as described above before. In the desalting step, the last eight fractions were reduced to four fractions by loading two fractions on one cartridge, giving a total of 14 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that ATM and p53 coordinately regulated FoxM1 to modulate responses and resistance to epirubicin in breast cancer [19]. It has been shown that PLK1 plays a role in DNA damage recognition with homologous recombination repair and has been involved in multidrug resistance [44][45][46]. Based on the interaction between FoxM1 and its downstream genes, FoxM1 could be used as a therapeutic target to overcome acquired resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the direct patient tumor models, surgical samples are implanted into immunodeficient mice, thus preserving key features that cells in culture irreversibly lose (30). Thus, these testing platforms are useful for translational research as in vivo hypothesis testing can keep pace with subsequent phases of clinical development, integrating as well pharmacologic assay development (11,14,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical work, leading to this clinical trial, we hypothesized that interrogating the integrative response of a tumor to a pharmacologic insult with gemcitabine would provide rationale for combinatorial strategies. Using a dynamic, fine-needle aspirate-based ex vivo gemcitabine exposure assay on 11 PDA cases with known gemcitabine sensitivity, we found that the common feature of resistant cases was the inability of gemcitabine to induce a downregulation of Plk1 mRNA expression (16). Further mechanistic studies indicate that Plk1 was a mediator of gemcitabine susceptibility and cotreatment with siRNA against Plk1 gene synergized the in vitro antiproliferative effects of gemcitabine.…”
Section: Introductionmentioning
confidence: 91%